Análisis comparativo del ciclo de vida para la huella de carbono de un vehículo a gasolina y un vehículo eléctrico. - Unocc Godoy, Omar Alexis; Durand Angeles, Brayan Sergio; SILVA, Fernando; Gómez Montoya, Juan Pablo (LACCEI, 2024)
This work presents the results of a comparative analysis of the carbon footprint between an electric vehicle (EV) and a gasoline vehicle (ICEV) from the manufacturing stage to the recycling process. Various variables were considered, such as the electrical energy generation matrix in South Korea for the manufacturing of vehicles and the energy matrix of Peru for operation in different mileage scenarios. As a case study, two Hyundai brand vehicles were analyzed, collecting information on their technical characteristics provided by the manufacturer. CO2 emissions were calculated, taking into account the carbon footprint coefficients of the various variables in each stage of the life cycle. The results obtained in different mileage scenarios show that, for shorter distances, the difference in average gCO2 emissions between the gasoline vehicle and the electric vehicle is minimal. However, in higher mileage scenarios, the gCO2 difference is significantly larger for gasoline vehicles. These results indicate a positive impact on the reduction of greenhouse gases in Peru, highlighting the importance of these findings for making decisions that favor the environment. In addition, the need to create social awareness about the levels of greenhouse gases is highlighted to accelerate the change in the country's energy grid.